Heat preservation material charging process for producing lithium battery negative electrode material

By adopting a new insulation material furnace loading process in the production process of lithium battery negative electrode materials, the problems of more auxiliary materials and high power supply unit consumption in the existing process are solved, and the effects of reducing the amount of coke after calcination, improving the quality of finished products and shortening the production cycle are achieved.

CN119873813APending Publication Date: 2025-04-25GUIZHOU ANTEP NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458550.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing lithium battery negative electrode material production process has problems such as high auxiliary materials, high power supply single consumption, high risk of spraying furnaces, insufficient sulfur discharge, too low pH value and extended cooling cycle, resulting in high production costs and low output.

Method used

A new insulation furnace loading process is adopted, including laying calcined coke and carbon black of different particle sizes in the cabin, filling the carbon black and graphite powder, setting graphite conductive columns and circular exhaust holes, and reasonably adjusting the power supply curve to achieve graphitization with the lowest single consumption.

Benefits of technology

It effectively reduces the amount of coke after calcination, reduces the total height of the furnace, enhances the breathability of the graphitization furnace, increases the pH value of the finished product, reduces the specific surface area, and shortens the graphitization production cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091187180000041
    Figure BDA0005091187180000041
  • Figure BDA0005091187180000051
    Figure BDA0005091187180000051
Patent Text Reader

Abstract

The invention discloses a heat preservation material charging process for producing a lithium battery negative electrode material, which is characterized in that a part of calcined coke heat preservation material with the granularity of 3-8 is replaced by calcined coke with the granularity of 8-25, and the height is reduced by 10cm; according to the present invention, 0.2-2 cm of the calcined coke is adjusted to 80 cm from the conventional 110 cm, the final charging total height is reduced by 30-40 cm, and the above modification does not reduce the quality of the finished product, the use amount of the calcined coke is reduced and the charging total height is reduced on the premise of ensuring the quality of the finished product, the use amount of the calcined coke in each furnace can be reduced by 40-50 tons in the furnace body specification of 26.8 m * 4.2 m * 2500 mm, the gas permeability of the graphitization furnace is enhanced, and the production cost is reduced. The PH value of a final finished product is increased, the specific surface area of the product is reduced, the cooling time is shortened, and the graphitization production period is further shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of production of negative electrode materials for lithium batteries, and in particular to a process for charging a furnace with heat-insulating materials for producing negative electrode materials for lithium batteries. Background Art

[0002] The production of lithium batteries is inseparable from artificial graphite. Graphitization is a key process in the production of artificial graphite. It mainly uses thermal activation to transform thermodynamically unstable carbon atoms from a chaotic layer structure to a graphite crystal structure in an orderly manner. The industry currently uses the graphitization Acheson box furnace production process, which uses refractory bricks, graphite electrode strips, and graphite blocks to build a box body. Semi-graphite materials are used to make box plates of varying specifications (including bottom plates, side plates, upper covers, and baffles). Graphite powder is laid under the bottom plate, and carbon black powder is filled between the side plates and the outer furnace body, eventually forming a box body with a length of 26.8m, a width of 4.2m, and 2500mm filled with lithium battery negative electrode materials (powder).

[0003] Calcined coke is the product of high-temperature calcination of petroleum coke. It eliminates moisture, volatiles, volume shrinkage, increases strength, and reduces resistivity. It can be used as a heat preservation material in the production process of graphitization of lithium battery negative electrodes. The specifications of the calcined coke furnace in the current process are: 10 cm of calcined coke with a particle size of 8 to 25, 30 cm of calcined coke with a particle size of 3 to 8, and 110 cm of calcined coke with a particle size of 0.2 to 2 are laid above the cover from bottom to top, and the total furnace height is 140 to 150 cm. The existing process has the following disadvantages:

[0004] (1) Excessive use of auxiliary materials increases production costs;

[0005] (2) High power consumption per unit;

[0006] (3) Increased risk of furnace spraying, insufficient sulfur discharge and low pH value;

[0007] (4) The cooling period is extended and the output is low. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the existing defects and provide a heat-insulating material loading furnace process for producing lithium battery negative electrode materials, which can effectively solve the problems in the background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: a process for charging a heat preservation material into a furnace for producing a negative electrode material for a lithium battery, comprising the following steps:

[0010] Step S1: On the bottom of the compartment, 50 cm high A-type calcined coke is laid and compacted, and then 50 cm of carbon black is laid on the A-type calcined coke and compacted, so that the total height of the bottom auxiliary materials is placed 10 cm at the bottom electrodes at both ends of the compartment conductive wall;

[0011] Step S2: hoisting the graphite bottom plate and the column graphite compartment plates around the furnace core;

[0012] Step S3: Fill the side wall of the furnace core with carbon black at a distance of 80 cm from the inner side of the furnace wall, and compact it every 50 cm until it is 10 cm away from the upper end of the graphite compartment plate of the furnace core;

[0013] Step S4: Fill the positive and negative conductive walls of the furnace core with graphite powder at a distance of 40 cm from the furnace wall, and compact it in a layer of 50 cm until it is flush with the upper end of the graphite compartment plate of the furnace core;

[0014] Step S5: The negative electrode raw material is laid flat into the furnace, one layer every 50 cm, and 8 rows of graphite conductive columns are laid between each layer. Each furnace has 5 layers of negative electrode raw material and 4 layers of graphite conductive columns;

[0015] Step S6: After the negative electrode raw material is put into the furnace, the upper layer is sealed with a graphite cover plate;

[0016] Step S7: Laying three layers of insulation material on the cover plate, the first layer of B-type calcined coke is 20 cm, the second layer of C-type calcined coke is 10 cm, and the third layer of D-type calcined coke is 80 cm;

[0017] Step S8: Each furnace is provided with 55 circular exhaust holes with a diameter of 60 cm evenly distributed above the B-type calcined coke;

[0018] Step S9: After the furnace is loaded, a corresponding power transmission curve is formulated according to the material characteristics and the technical indicators of the finished product, and the power of each heating stage is reasonably adjusted to complete the graphitization of the negative electrode material with the lowest unit consumption.

[0019] As a preferred technical solution of the present invention, the type A calcined coke in step S1 is calcined coke with a particle size of 0.2 to 3.

[0020] As a preferred technical solution of the present invention, the carbon black resistance in step S1 is not less than 2000Ω.

[0021] As a preferred technical solution of the present invention, in step S2, the furnace core is 2.5m high, 4m wide, and 25.5m long, the plate thickness is 8cm, the spacing is 80cm, and the graphite compartment plates are used to separate the internal space of the furnace body.

[0022] As a preferred technical solution of the present invention, the specifications of the graphite conductive column in step S5 are 120 cm in length, 20 cm in width and 20 cm in height.

[0023] As a preferred technical solution of the present invention, in step S6, the gap between the cover plates is not less than 3 mm.

[0024] As a preferred technical solution of the present invention, the B-type calcined coke in step S7 and step S8 is calcined coke with a particle size of 8 to 25.

[0025] As a preferred technical solution of the present invention, the C-type calcined coke in step S7 is calcined coke with a particle size of 3 to 8.

[0026] As a preferred technical solution of the present invention, the D-type calcined coke in step S7 is calcined coke with a particle size of 0.2 to 2.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: under the premise of ensuring the quality of the finished product, the process reduces the amount of calcined coke used and reduces the total height after the furnace is loaded. In the furnace body specification of 26.8m*4.2m*2500mm, the process can reduce the amount of calcined coke used in each furnace by 40 to 50 tons, and enhances the air permeability of the graphitization furnace, improves the pH value of the final product, reduces the specific surface area of ​​the product, reduces the cooling time and thus shortens the graphitization production cycle. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention provides a technical solution: a process for charging a heat preservation material into a furnace for producing a negative electrode material for a lithium battery, characterized in that it comprises the following steps:

[0030] Step S1: On the bottom of the compartment, 50 cm high A-type calcined coke with a particle size of 0.2-3 is laid and compacted, and then 50 cm of carbon black is laid on the A-type calcined coke and compacted, and the resistance of the carbon black is not less than 2000Ω, so that the total height of the bottom auxiliary material is placed 10 cm at the bottom electrodes at both ends of the compartment conductive wall;

[0031] Step S2: hoisting the graphite bottom plate and the column graphite compartment plates around the furnace core, the furnace core is 2.5m high, 4m wide, and 25.5m long, the plate thickness is 8cm, and the spacing is 80cm. The graphite compartment plates are used to separate the internal space of the furnace body;

[0032] Step S3: Fill the side wall of the furnace core with carbon black at a distance of 80 cm from the inner side of the furnace wall, and compact it every 50 cm until it is 10 cm away from the upper end of the graphite compartment plate of the furnace core;

[0033] Step S4: Fill the positive and negative conductive walls of the furnace core with graphite powder at a distance of 40 cm from the furnace wall, and compact it in a layer of 50 cm until it is flush with the upper end of the graphite compartment plate of the furnace core;

[0034] Step S5: The negative electrode raw material is laid flat into the furnace, one layer every 50 cm, and 8 rows of graphite conductive columns are laid between each layer. Each furnace has 5 layers of negative electrode raw material and 4 layers of graphite conductive columns. The specifications of the graphite conductive columns are 120 cm long, 20 cm wide and 20 cm high;

[0035] Step S6: After the negative electrode raw material is put into the furnace, the upper layer is sealed with a graphite cover plate. In step S6, the gap between the cover plates is not less than 3 mm;

[0036] Step S7: Laying three layers of insulation material on the cover plate, the first layer is 20 cm of B-type calcined coke with a particle size of 8-25, the second layer is 10 cm of C-type calcined coke with a particle size of 3-8, and the third layer is 80 cm of D-type calcined coke with a particle size of 0.2-2;

[0037] Step S8: Each furnace is provided with 55 circular exhaust holes with a diameter of 60 cm evenly distributed above the B-type calcined coke;

[0038] Step S9: After the furnace is loaded, a corresponding power transmission curve is formulated according to the material characteristics and the technical indicators of the finished product, and the power of each heating stage is reasonably adjusted to complete the graphitization of the negative electrode material with the lowest unit consumption.

[0039] The innovation of this process is that part of the calcined coke insulation material with a particle size of 3-8 is replaced by calcined coke with a particle size of 8-25, and the height is reduced by 10cm; the calcined coke with a particle size of 0.2-2 is adjusted from the conventional 110cm to 80cm, and finally the total furnace height is reduced by 30-40cm, and the above changes do not reduce the quality of the finished product.

[0040] In the specific implementation of this process, we recorded the quality of some finished products, as shown in the following table:

[0041] Table 1 Finished product quality record table Part 1

[0042] In Table 1, Dmin, D00, Dx(10), Dx(50), Dx(90), D99, and D100 are particle size parameters, SD10, SD50, and SD90 are specific discharge capacity parameters, SSA is a specific surface area parameter, TAP is a tapping parameter, PH is acidity and alkalinity, and carbon content is carbon content.

[0043]

[0044] Table 2 Finished product quality record table Part 2

[0045] In Table 2, Dmin, Dmax, D00, D10, D50, D90, Dx(10), Dx(50), Dx(90), D99, and D100 are particle size parameters, SD10, SD50, and SD90 are specific discharge capacity parameters, SSA is specific surface area parameter, and PH is pH.

[0046] Under the premise of ensuring the quality of the finished product, this process reduces the amount of calcined coke, reduces the total height after loading, enhances the air permeability of the graphitization furnace, improves the pH value of the final product, reduces the specific surface area of ​​the product, reduces the cooling time and thus shortens the graphitization production cycle.

[0047] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for charging a heat preservation material to produce a negative electrode material for a lithium battery, characterized in that: The following steps are involved: Step S1: On the bottom of the compartment, 50 cm high A-type calcined coke is laid and compacted, and then 50 cm of carbon black is laid on the A-type calcined coke and compacted, so that the total height of the bottom auxiliary materials is placed 10 cm at the bottom electrodes at both ends of the compartment conductive wall; Step S2: hoisting the graphite bottom plate and the column graphite compartment plates around the furnace core; Step S3: Fill the side wall of the furnace core with carbon black at a distance of 80 cm from the inner side of the furnace wall, and compact it every 50 cm until it is 10 cm away from the upper end of the graphite compartment plate of the furnace core; Step S4: Fill the positive and negative conductive walls of the furnace core with graphite powder at a distance of 40 cm from the furnace wall, and compact it in a layer of 50 cm until it is flush with the upper end of the graphite compartment plate of the furnace core; Step S5: The negative electrode raw material is laid flat into the furnace, one layer every 50 cm, and 8 rows of graphite conductive columns are laid between each layer. Each furnace has 5 layers of negative electrode raw material and 4 layers of graphite conductive columns; Step S6: After the negative electrode raw material is put into the furnace, the upper layer is sealed with a graphite cover plate; Step S7: Laying three layers of insulation material on the cover plate, the first layer of B-type calcined coke is 20 cm, the second layer of C-type calcined coke is 10 cm, and the third layer of D-type calcined coke is 80 cm; Step S8: Each furnace is provided with 55 circular exhaust holes with a diameter of 60 cm evenly distributed above the B-type calcined coke; Step S9: After the furnace is loaded, a corresponding power transmission curve is formulated according to the material characteristics and the technical indicators of the finished product, and the power of each heating stage is reasonably adjusted to complete the graphitization of the negative electrode material with the lowest unit consumption.

2. The process for charging a heat preservation material into a furnace for producing negative electrode materials for lithium batteries according to claim 1, characterized in that: In the step S1, the type A calcined coke is calcined coke with a particle size of 0.2 to 3.

3. The process for charging a heat preservation material into a furnace for producing a negative electrode material for a lithium battery according to claim 1, characterized in that: In the step S1, the resistance of the carbon black is not less than 2000Ω.

4. The process for charging a heat preservation material into a furnace for producing anode materials for lithium batteries according to claim 1, characterized in that: In step S2, the furnace core is 2.5 m high, 4 m wide, and 25.5 m long, the plate thickness is 8 cm, the spacing is 80 cm, and the graphite compartment plates are used to separate the internal space of the furnace body.

5. The process for charging a heat preservation material into a furnace for producing negative electrode materials for lithium batteries according to claim 1, characterized in that: The specifications of the graphite conductive column in step S5 are 120 cm in length, and 20 cm in width and height.

6. The process for charging a heat preservation material into a furnace for producing negative electrode materials for lithium batteries according to claim 1, characterized in that: In step S6, the gap between the cover plates is not less than 3 mm.

7. The process for charging a heat preservation material into a furnace for producing negative electrode materials for lithium batteries according to claim 1, characterized in that: The B-type calcined coke in step S7 and step S8 is calcined coke with a particle size of 8 to 25.

8. The heat preservation material charging process for producing negative electrode materials for lithium batteries according to claim 1, characterized in that: The C-type calcined coke in step S7 is calcined coke with a particle size of 3 to 8.

9. The process for charging a heat preservation material into a furnace for producing negative electrode materials for lithium batteries according to claim 1, characterized in that: The D-type calcined coke in step S7 is calcined coke with a particle size of 0.2-2.